2011
DOI: 10.4102/sajems.v14i2.61
|View full text |Cite
|
Sign up to set email alerts
|

A critical analysis of the contents of the IFRS for SMEs - a South African perspective

Abstract: The IFRS for SMEs was developed to address the reporting needs of SMEs worldwide. SMEs however do not necessarily have a global focus. Furthermore, SMEs from different parts of the world are exposed to different conditions and environments.Although the IFRS for SMEs was not intended for a specific user group, the majority of the respondents to the Exposure Draft on IFRS for SMEs were from Europe and other developed countries while only limited respondents from Africa and developing countries were involved.This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Their understanding appeared to be based on their individual dealings with SMEs. This is in line with existing literature, which indicates that a variety of definitions may be ascribed to the term 'SME' (DTI 2008b;IASB 2015a;Schutte & Buys 2011b;South Africa 1996;Tudor & Mutiu 2008).…”
Section: Undervaluing Of the International Financial Reporting Standards For Small And Medium-sized Entities By South African Practitionesupporting
confidence: 89%
See 2 more Smart Citations
“…Their understanding appeared to be based on their individual dealings with SMEs. This is in line with existing literature, which indicates that a variety of definitions may be ascribed to the term 'SME' (DTI 2008b;IASB 2015a;Schutte & Buys 2011b;South Africa 1996;Tudor & Mutiu 2008).…”
Section: Undervaluing Of the International Financial Reporting Standards For Small And Medium-sized Entities By South African Practitionesupporting
confidence: 89%
“…None of the interviewees suggested that a specific topic in IFRS for SMEs was either misplaced or irrelevant in respect of serving the needs of the SME sector, further emphasising the appropriateness of the standard for SMEs. Prior studies have also shown that the content of IFRS for SMEs is suitable for the South African environment (Schutte & Buys 2011a, 2011b.…”
Section: Contents Of the International Financial Reporting Standards For Small And Medium-sized Entitiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, literature reported that capital market investors, in particular, required a more transparent and high-quality financial report that would make the comparability of financial statement possible (Amiram, 2012;Matthew, 2009;Schutte & Buys, 2011;Shima & Yang, 2012).…”
Section: Background To the Studymentioning
confidence: 99%
“…The debate around the new standard involves several factors, including: the comments on the IASB's Discussion Paper (Evans et al, 2005) and the Exposure Draft ‗IFRS for Small and Medium-Sized Entities' (Di Pietra et al, 2008); the different perspectives of acceptance among users, preparers and European Countries (Quagli & Paoloni, 2012); and the factors influencing countries' adoption of the IFRS for SMEs (Kaya & Koch, 2015). A number of contributions have referred to country-specific perspectives, such as those of the Czech Republic (Albu et al, 2013;Nerudova & Bohusova, 2008;Pàlka & Svitàkovà, 2011), Estonia (Alver et al, 2014), Germany (Eierle & Haller, 2009;Kreipl et al, 2014), Ghana (Aboagye-Otchere & Agbeibor, 2012), Greece (Mandilas et al, 2010) Italy (Baldarelli et al, 2007;Cisi, 2008), the Netherlands (Litjens et al, 2012), Romania (Albu et al, 2010;Gîrbină et al, 2012), South Africa (Schutte & Buys, 2011;Stainbank, 2008;van Wyk & Rossouw, 2009), Spain (Milanés Montero et al, 2011), Turkey (Arsoy et al, 2007;Atik, 2010;Kiliç et al, 2016;Turegun & Kaya, 2014), the United Arab Emirates (Kumar, 2014) and the USA (Jermakowicz & Epstein, 2010). Nevertheless, despite some prior studies having analysed similarities and differences between the IFRS for SMEs and certain accounting settings -namely, the EU Accounting Directives (EFRAG, 2010), local GAAP (Albu et al, 2010;Buculescu & Velicescu, 2014;Cisi, 2008;EFAA, 2010;Girbina et al, 2012), and full IFRS as well …”
Section: Introductionmentioning
confidence: 99%